Hambatan Mahasiswa Teknik Elektro dalam Mengikuti Proses Pembelajaran Daring - Rahmat Fadil; Riki Mukhaiyar (Jurnal Pendidikan Teknik Elektro, 2022)
This study aims to determine the description of Electrical Engineering Students' Barriers to Online Learning. This research method uses a quantitative descriptive method, which means that this research method aims to create a description or descriptive of an objective that uses numbers, starting from data collection, interpretation of the data and appearance and results. The research instrument used a questionnaire distributed to students majoring in Electrical Engineering class of 2020 who carried out online learning, totaling sixty-five students. Assessment of research instruments using a Likert scale. The data analysis used is a descriptive statistical approach using the average mean, standard deviation values, and category scores of one to five to determine the extent of the distribution of the data. The results showed that the electrical engineering students' barriers to online learning had different category levels for each indicator, in the high category there were facilities indicators in the medium category, there were three indicators, namely indicators of psychological barriers, indicators of educators or lecturers and family indicators. So it can be concluded that the obstacles experienced by students majoring in Electrical Engineering in online learning come from psychological barriers, lecturers or educators, facilities and families. These factors trigger students to be less motivated to carry out online learning so that online learning is less effective and efficient.